KETRAMPILAN MANAJER KEPALA SEKOLAH, IKLIM SEKOLAH DAN KINERJA GURU MTs (MADRASAH TSANAWIYAH) DI KABUPATEN MADIUN - Sudarmiani Sudarmiani (Jurnal Pendidikan, 2008)
The objectives  of this research is to serve for description  about the significance of  managerial    skill  of  the  head-masters    and  the school's   culture towards the teachers' performance at the state and private   MTs  in  Madiun   District.   The  population   of  this  research includes  651  teachers,  and the  sample  drawn  out of the population covers 90 teachers. The  techniques   of  accumulating the data are questionnaire and documentation. The data  analysis techniques applied are descriptive  statistics  and inferential  statistics  under multiple regression  statistic technique.  The analysis on the data results in conclusion   that there is a significance   influence  of the managerial skill of the head-masters  and the schools'  culture towards the teachers' performance     at the  state  and private  MTs  in Madiun  District   (the working F= 32.331 > table F = 2.000). The significance of the managerial skill  of the head-masters   towards  the teachers'  'performance is also put  in research.  The  research   also  put in description  about  the managerial   skill  of the  head-masters,    the schools' culture and  the teachers'   performance   at state and private  MTs in Madiun District.